The insane Chicago way: the daring plan by Chicago gangs to create a Spanish mafia - Hagedorn, John (University of Chicago Press, 2015)
Intro -- Contents -- List of Illustrations -- Preface: This is Not a Movie -- Introduction: Lifting the Veil -- Part One: Ambitions -- 1. The Hit -- 2. The Old Man and the C- Note -- 3. The Transition from Turf to Profits -- Part Two: Organization -- 4. Spanish Growth and Development -- 5. "Two Dagos, Two Spics, and a Hillbilly" -- 6. Family Feuds -- Part Three: Corruption -- 7. Envelopes and Ethnic Politics -- 8. Police Corruption from the Suites to the Streets -- Part Four: Catastrophe -- 9. Ecstasy and Agony -- 10. The War of the Families -- 11. The Future of Gangs in Chicago -- Notes -- Appendix 1. Major Events in Chicago Gang History Prior to SGD -- Appendix 2. The Ten Years of SGD, Significant Events -- Appendix 3. Factual Charges of Ambrose on La Raza to SGD Board -- Appendix 4. SGD Grievance Format -- Appendix 5. Independence of the SGD Within the Organization -- Appendix 6. Grievance of the ISC Against the Latin Eagles -- Appendix 7. By-Laws of the Insane Family -- Appendix 8. Application of the C-NoteS for SGD Membership -- Appendix 9. Leyes of the SGD Union -- Index.